COOPERATION ISSUES IN THE INVESTIGATION AND DETECTION OF FRAUD - Xujamuratov Bekzod Uktamovich (Scholar Express Journals, 2024)
This article discusses the issues of interaction between investigative bodies and bodies engaged in operational investigative activities, the tasks of inquiry, investigative, operational units and internal affairs bodies, procedural independence of investigators and bodies of inquiry, non-interference in procedural activities during the investigation and disclosure of fraud crimes
Keywords: Inquiry; investigator; operational units